Association of Antenatal Corticosteroid use with Hypoglycaemia and Hyperbilirubinemia in Preterm Neonates Admitted in a Tertiary Hospital of Kolkata: A Longitudinal Study (Indian Journal of Public Health Research & Development, 2023)
AbstractBackground: Timely use of antenatal corticosteroids in a mother of preterm labour decreases the rates ofperinatal death, respiratory distress syndrome, intra-ventricular hemorrhage, necrotizing enterocolitis inthe new borns. However it is reported to have a causative role in neonatal hypoglycemia and hyperbilirubinemia.So the present study attempts to determine the association between the use of antenatal corticosteroids withhypoglycaemiaand hyperbilirubinemia in newborns with less than 35 weeks of gestational age.Methods: A prospective observational study was conducted during a time period of 24 months from January 2020to December 2021 in a tertiary care hospital of Kolkata on 99 preterm neonates of less than 35 weeks of gestationalage. Antenatal history of corticosteroid use, neonatal glucose level and bilirubin level were measured amongothers. Data were analyzed using MS-EXCEL.Results: Majority of neonates’ mothers (71.7%) had received antenatal corticosteroids. Only 4.0% of the cases hadhypoglycaemia at birth. But there was no cases of hypoglycaemia at 12 hour and 24 hour after birth. In 58.6% ofthe cases bilirubin level was in the phototherapy range and double surface photo therapy was required. In 14.1%of the cases double volume exchange transfusion was required.Conclusion: Antenatal corticosteroid administration is not associated with neonatal hypoglycaemia but it issignificantly related to neonatal hyperbilirubinemia.
Keywords: corticosteroid, preterm, hypoglycaemia, hyperbilirubinemia